Asymmetric Synthesis of Gonioheptolide A Analogues via an Organocatalytic Aldol Reaction as the Key Step - Enders, Dieter; David, Sarah; Deckers, Kristina; Greb, Andreas; Raabe, Gerhard (Synthesis, 2012)
An efficient asymmetric synthesis of the potential antitumor agent (–)-gonioheptolide A derivatives is described. By employing an (S)-proline-catalyzed aldol reaction, the RAMP hydrazone α-alkylation methodology, and a diastereoselective reduction with zinc borohydride five stereocenters are established in the target compound. 4-epi-Methoxy-gonioheptolide A was obtained in ten steps in 15% overall yield and excellent diastereo- and enantiomeric excesses (de ≥95%, ee ≥99%).
Keywords: dihydroxyacetone; aldol reaction; organocatalysis; proline; styryllactone